Turkism as a Marker of the Ukrainian Linguoculture in the 16th-17th Centuries - Grytsenko, Svitlana; Medynska, Natalia; Dudko, Iryna (Journal of History Culture and Art Research, 2020)
The cultural development cannot help displaying the language development as a whole, though it has its brightest reflection in vocabulary. There are no “pure languages” that would have evolved for over the millennia without any influence of the linguistic environment and neighbors. Ukraine's entry to the European cultural and educational sphere in the 16th-17th centuries contributed to spread and use on its territories such languages as: Ukrainian, Church Slavonic, Greek, Latin, Hebrew, Yiddish, Armenian, Turkish, Kipchat-Tatar, Polish, German, Hungarian, Moldovan, Italian, French, etc. Written sources of the Ukrainian language of the 16th-17th centuries demonstrate the results of linguistic symbiosis – borrowings from different languages, among that Turkism is quantifiable. Borrowings from the Turkic languages are presented in almost all thematic groups of vocabulary, except for the judiciary, the mental activity (mental state) of a person, their language activity, influence, and will. The majority of Turkism is represented in the military sphere, which was caused by the long wars of Ukraine with the Turkic-speaking states, and also in the field of marking imported Eastern goods, in particular the names of fabrics, clothing, dishes, spices, seasoning, etc. Most of these lexemes function in modern Ukrainian language. Ukrainian linguists have done the first steps in the context of studying Ukrainian-Turkic interaction and outlined the main periods of Turkic-speaking influence, ways of the Turkism introduction into the Ukrainian language. However, there are also some gaps in the study of this problem, such as research on the influence of Turkic languages at different chronological levels of the Ukrainian language development and their role in forming the Ukrainian linguistic world. This paper will help closing these gaps.